2022
DOI: 10.1210/clinem/dgac283
|View full text |Cite
|
Sign up to set email alerts
|

Remnant Cholesterol Predicts Long-term Mortality of Patients With Metabolic Dysfunction–associated Fatty Liver Disease

Abstract: Context Elevated serum remnant cholesterol independently predicts risks of cardiovascular diseases. However, the association between remnant cholesterol and metabolic dysfunction-associated fatty liver disease (MAFLD) remains unclear. Objectives This study aimed to explore the association of remnant cholesterol with MAFLD and its long-term mortality. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…Some scholars suggest that RC, rather than LDL-c, is linked to the development of cardiovascular disease [11]. Further studies have confirmed that RC not only predicts the risk for cardiovascular disease, but also the risk of metabolic disease [13,23,24]. Hyperuricemia and cardiovascular diseases share common risk factors [25].…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars suggest that RC, rather than LDL-c, is linked to the development of cardiovascular disease [11]. Further studies have confirmed that RC not only predicts the risk for cardiovascular disease, but also the risk of metabolic disease [13,23,24]. Hyperuricemia and cardiovascular diseases share common risk factors [25].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have confirmed that remnant cholesterol, not HDL-C or LDL-C, is significantly associated with an increased risk of CVD [ 17 , 18 ]. A higher level of remnant cholesterol was also related to the prevalence of CKD in a general middle-aged population [ 19 ] and was predictive of all-cause, cardiovascular-related, and cancer-related mortality in individuals with MAFLD [ 20 ]. In our study, we demonstrated that remnant cholesterol was independently related to an increased risk of CKD in all subjects after PSM, as well as in individuals with MAFLD with DM or prediabetes, which suggests that elevated serum remnant cholesterol might contribute to the development of CKD in subjects with MAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…In a secondary analysis of PREDIMED study, a primary prevention trial, the Rem-C at least 30 mg/dl was associated with increased MACE events (HR 1.89), independently of LDL-C 100 or less or greater than 100 mg/dl [24]. In a 25-year observational cohort of high-risk NHANES cohort, a similar Rem-C level 33 versus 22 mg/dl was associated with a 2.35-fold increased rate of cardiovascular deaths and a 2.18-fold increased risk of allcause deaths [25], with a much weaker relationship with triglyceride levels. Finally in a cohort of type 2 diabetes mellitus and recent-onset CKD (stage 3-5), Rem-C versus > 30 mg/dl was associated with a multivariate-adjusted OR of 1.70 for cardiovascular deaths after a follow-up of less than 2.0 years, which remained significant regardless of LDL-C or >100 mg/dl [26].…”
Section: Remnant Cholesterol and Long-term Cardiovascular Outcomes: O...mentioning
confidence: 95%